engagement of visual novel digital game entitled single mingle: Career versus marriage - Siti Nur Farah Natasha Azhar; Erni Marlina Saari; Norshahila Ibrahim; Fadhlina Mohd Razali; Noor Hidayah Azmi (Journal of ICT in Education, 2022)
This study is about the development of a Visual Novel game “SINGLE MINGLE: Career vs Marriage”. The game project focused on developing the game individually either in 2D or 3D. This game is created fully in 2D with its own message to be delivered. The objective of this study is to show the process of game development which can be used to solve several current issues that were chosen during pitching. This paper is to focus on the purpose and creation of the game “SINGLE MINGLE” from the very beginning. The project phases are divided into three main phases which include pre-production, production, and post-production. Marketing items such as posters and merchandise were designed and digitalized in the post-production phase. The affirmative end product from the players shows that in spite of single or married ladies, this game really makes them engaged because of the appealing game design interface and interesting gameplay.